2020
DOI: 10.1152/physrev.00011.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Physiology of Pendrin-Positive Intercalated Cells

Abstract: Intercalated cells (ICs) are found in the connecting tubule and the collecting duct. Of the three IC subtypes identified, type B intercalated cells are one of the best characterized and known to mediate Cl absorption and HCO3 secretion, largely through the anion exchanger pendrin. This exchanger is thought to act in tandem with the Na+-dependent Cl/HCO3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 245 publications
(406 reference statements)
1
55
0
Order By: Relevance
“…Finally, cross-sectional analysis revealed that the pendrin levels in urinary EVs are significantly correlated with ARR. These data are consistent with experimental studies showing the stimulation of pendrin in a state of aldosterone excess, suggesting its role in aldosterone-induced fluid and electrolyte abnormalities [7,10,11,17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, cross-sectional analysis revealed that the pendrin levels in urinary EVs are significantly correlated with ARR. These data are consistent with experimental studies showing the stimulation of pendrin in a state of aldosterone excess, suggesting its role in aldosterone-induced fluid and electrolyte abnormalities [7,10,11,17].…”
Section: Discussionsupporting
confidence: 91%
“…Excessive production of the steroid hormone aldosterone results in increased activity of NaCl-transporting proteins in renal tubules, thereby increasing fluid volume and blood pressure (BP). Experimental evidence indicates that apical membrane channels and transporters such as the epithelial Na + channel (ENaC), Na-Cl-cotransporter (NCC), and Cl − /HCO 3 − exchanger pendrin are dysregulated under aldosterone excess [6][7][8]. However, few studies have examined whether the reported mechanisms in animal models apply to PA in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B-type cells, on the other hand, express a different anion exchanger, pendrin, in their apical membrane, and they lack AE1 ( 110 ). Pendrin-positive cells (which are restricted to the cortex and, to a much lesser extent, the outer stripe of the outer medulla) can express V-ATPase not only in intracellular vesicles but also to different degrees in their apical and/or basolateral membranes ( 111 ). Cells that express apical V-ATPase, but no basolateral AE1, were initially categorized as non-A, non-B cells ( 112 ), and subsequently they were shown to also express apical pendrin alongside the V-ATPase ( 110 ).…”
Section: V-atp Ase Expression Proton Secretion and Organ Functionmentioning
confidence: 99%
“…Similarly, downstream ENaCβ in the principal cells of CD for tubular salt reabsorption was enhanced ( 32 , 33 ). Of note, pendrin as a Cl − /HCO3 − exchanger expressed in the apical region of distal tubules and involved in the tubular Cl − absorption and HCO3 − secretion was augmented ( 34 ). Activation of pendrin-mediated Cl − absorption has also been reported in NCC KO mice ( 35 ).…”
Section: Discussionmentioning
confidence: 99%